2020
DOI: 10.1002/oby.22709
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Physical Activity and Incidence and Remission of Overall and Abdominal Obesity in 113,950 Adults

Abstract: Objective This study examined the dose‐response relationship between changes in physical activity (PA) and subsequent incidence or remission of overall and abdominal obesity. Methods A total of 113,950 healthy individuals aged ≥ 18 years participating in the Taiwan MJ Cohort were included. Two‐year changes in PA between the first and second examination were linked to subsequent development and remission of overall and abdominal obesity. Results During a mean 5.6‐year follow‐up after the second examination, 9,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Discrepancies in the association between PA and obesity/AO have been reported across different populations owing to variations in genetic and nongenetic factors. 10,27-29 This study reported that those who performed low levels of vigorous PA had higher odds of developing AO instead of obesity. Notably, the reduction in WC in older Japanese adults has been shown to effectively decrease the risk of developing type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 77%
“…Discrepancies in the association between PA and obesity/AO have been reported across different populations owing to variations in genetic and nongenetic factors. 10,27-29 This study reported that those who performed low levels of vigorous PA had higher odds of developing AO instead of obesity. Notably, the reduction in WC in older Japanese adults has been shown to effectively decrease the risk of developing type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 77%
“…According to the criteria of the Ministry of Health and Welfare, Taiwan, the criteria of metabolic syndrome for Taiwanese require three or more of the following measurements: (1) abdominal obesity: waist circumference >90 cm (35 inches) for men and >80 cm (31 inches) for women [ 45 ]; (2) hypertension: raised blood pressure (BP): systolic BP ≥ 130 mmHg or diastolic BP ≥ 85 mmHg or current use of antihypertensive drugs. Instead of applying the blood pressure data from the MJ database, this study used the long-term use of antihypertensive drugs as the proxy variable; (3) hyperglycemia: raised fasting plasma glucose (FPG): FPG ≥ 100 mg/dL or current use of antihyperglycemic drugs [ 46 ]; (4) hypertriglyceridemia: higher triglycerides (TG): TG ≥ 150 mg/dL or current use of antitriglyceride drugs; (5) lower high-density lipoprotein cholesterol (HDL-C): HDL-C <40 mg/dL for men and <50 mg/dL for women [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, a study by Cardenas et al reported an inverse association of leisure time PA with WC, abdominal obesity and BMI [ 41 ]. With regard to changes in PA levels over time, a large Asian cohort study reported that an increase in PA was associated with lower abdominal obesity [ 42 ]. However, a comparison between our research with other longitudinal studies is questionable, as most prior studies focused either on body weight change/obesity as outcome of interest [ 43 ], or on waist circumference as predictor variable [ 44 ], rather than outcome of interest like we did.…”
Section: Discussionmentioning
confidence: 99%